Student Engagement Tracks with Success In-person and Online in a Hybrid-Flexible Course - Zoya Adeel; Stefan M. Mladjenovic; Sara J. Smith; Pulkit Sahi; Abhay Dhand; Sarah Williams-Habibi; Kate Brown; Katie Moisse (Canadian Journal for the Scholarship of Teaching and Learning, 2023)
Some university students face barriers to learning in physical classrooms, while others are reluctant to return to in-person learning environments because of COVID-19. Hybrid-flexible (HyFlex) learning environments give students the option to participate in-person or virtually, but there are concerns about student engagement and success. In this pre-pandemic study, we conducted a program-wide survey to explore student perceptions of and experiences with a HyFlex teaching and learning platform (n=238). Our survey data revealed that 86.17% of students find features of this platform helpful when accessing, engaging with, and learning course content. This was particularly true among students who reported having a flexible learning need. We also compared engagement with the HyFlex teaching and learning platform (calculated as a score out of 100 based on attendance and participation in interactive slides) and final grades between students who chose to participate predominantly in-person or online in two HyFlex offerings during the 2019/20 academic year. We found no significant difference in engagement or final grade between in-person dominant and online dominant learners in either course. We found a moderate correlation between engagement and final grade in both courses, such that highly engaged students achieved high grades regardless of their preferred mode of attendance. Our findings suggest that giving students the option to learn in-person or virtually from class to class does not negatively affect engagement or success and may in fact support success among students with flexible learning needs. As Canadian universities emerge from the pandemic, our findings remind us to retain the flexibility that virtual teaching and learning affords to support our diverse student bodies.